Endoparasite of pupae of the chestnut transient moth - Borzykh, O.; Bashchenko, M.; Fedorenko, A.; Fedorenko, V.; Shita, O.; Chaika, V. (Quarantine and plant protection, 2024)
Goal. To conduct a search for endoparasites of pupae of the chestnut transient moth in natural conditions, to determine their species composition, biological and ecological features. Methods. Laboratories. Research was carried out during 2022—2023 in the pesticide application laboratory of the Institute of Plant Protection of the National Academy of Sciences. Collection of leaves was carried out in the Kyiv region (Obuhiv district) and the city of Kyiv (Gryshka botanical garden). Results. In the course of the study, it was established that from 1.0 kg of collected fallen leaves of common bitter chestnut at the first location (Kyiv region, Obukhivskyi district), 1.676 chestnut moth pupae were removed, of which 57.8% were females, and 42.2% were males. A total of 1.544 butterflies flew out (92.2% of the total number). As for the pupae from which the imagos of the chestnut transient moth did not emerge, 3.4% were infected with the entopathogenic fungus Beauveria bassiona V. (which usually affects the plants in which the pupae are located), and from the rest (4.4%) the imagoes of the endoparasite Pediobius saulius W. (females — 2.6%, males — 1.8%). At the second location (Gryshko Botanical Garden), 1.569 pupae were selected (females — 56.2%, males — 43.8%), from which 1.498 butterflies (95.5%) fledged as a result, and the remaining 1.7% are infected with the entopathogenic fungus Beauveria bassiona V. — 2.8% are infected with the endoparasite Pediobius saulius W. (females — 1.5%, males — 1.3%). Therefore, Pediobius saulius W. is a natural regulator of chestnut transient moth populations. Conclusions. According to the results of the calculations, per 1.0 kg of fallen leaves of common bitter chestnut, the average number of pupae of the chestnut transient moth was 1622.0 individuals, of which 57% were females and 43% were males. Infection of pupae with the entopathogenic fungus Beauveria bassiona V. — 2.55%, and infection with the endoparasite Pediobius saulius W. — 3.6%. The edoparosite belonged to the species Pediobius saulius (Walker, 1839), and its emergence in laboratory conditions was 10 days ahead of the emergence of the imago of the chestnut transient moth.